2017
DOI: 10.1038/cdd.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

A novel DLX3–PKC integrated signaling network drives keratinocyte differentiation

Abstract: Epidermal homeostasis relies on a well-defined transcriptional control of keratinocyte proliferation and differentiation, which is critical to prevent skin diseases such as atopic dermatitis, psoriasis or cancer. We have recently shown that the homeobox transcription factor DLX3 and the tumor suppressor p53 co-regulate cell cycle-related signaling and that this mechanism is functionally involved in cutaneous squamous cell carcinoma development. Here we show that DLX3 expression and its downstream signaling dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…We previously reported that epidermal Dlx3 deletion results in hyperproliferation, which is exacerbated with TPA treatment . We tested the effect of TPA treatment on DLX4 KO skin and detected no difference between WT and Dlx4 KO as assessed by morphology and quantification of epidermal thickness (Figure E,F).…”
Section: Resultsmentioning
confidence: 80%
“…We previously reported that epidermal Dlx3 deletion results in hyperproliferation, which is exacerbated with TPA treatment . We tested the effect of TPA treatment on DLX4 KO skin and detected no difference between WT and Dlx4 KO as assessed by morphology and quantification of epidermal thickness (Figure E,F).…”
Section: Resultsmentioning
confidence: 80%
“…Six different dominant acting DLX3 mutations causing TDO with marked phenotypic variability have been reported in humans . The most common mutation in DLX3 is a frameshift mutation (c.571_574delGGGG), resulting in recoding and truncating the C‐terminal transactivating domain of the DLX3 protein (p.Gly191ArgfsTer66) . Human TDO may be caused by loss of function and haploinsufficiency of DLX3 .…”
Section: Discussionmentioning
confidence: 99%
“…Hyper-keratosis, including hyper-proliferation and hyper-differentiation, arises from the epidermal dyshomeostasis in keratinocytes. [16][17][18][19] Given that most cutaneous toxicities induced by drugs (e.g., everolimus, adriamycin liposome, and capecitabine) are caused by cellular processes targeting keratinocytes, [20][21][22] we initially sought to test the direct effect of sorafenib on keratinocytes by employing human primary keratinocytes and HaCaT cells, the immortalized human keratinocytes which largely retained the differentiation capacity of normal epidermal cells. 24 We examined the states of proliferation and differentiation in keratinocytes, with keratin 5 (KRT5) and keratin 14 (KRT14) applied as proliferation markers, and keratin 1 (KRT1), keratin 10 (KRT10), loricrin (LORICRIN) and involucrin (IVL) characterizing differentiation.…”
Section: Vascular Endothelial Cells Contribute To Sorafenib-induced Hmentioning
confidence: 99%
“…[12][13][14][15] Hyper-keratosis, defined as stratum corneum thickening, generally results from the abnormality in epidermal homeostasis of keratinocytes, including hyperproliferation and hyper-differentiation. [16][17][18][19] Since numerous studies have uncovered that most drug-induced cutaneous toxicities are the aftereffects of pathways directly affecting keratinocytes, [20][21][22] keratinocyte dysfunction has thus been largely speculated as the main cause of sorafenib-induced HFSR. However, intervention strategies based on such concept are proven ineffective.…”
Section: Introductionmentioning
confidence: 99%